Frondanol, a Nutraceutical Extract from Cucumaria frondosa, Attenuates Colonic Inflammation in a DSS-Induced Colitis Model in Mice - Subramanya, Sandeep B.; Chandran, Sanjana; Almarzooqi, Saeeda; Raj, Vishnu; Al Zahmi, Aisha Salem; Al Katheeri, Radeya Ahmed; Al Zadjali, Samira Ali; Collin, Peter D.; Adrian, Thomas E. (Marine drugs, 2018)
Frondanol is a nutraceutical lipid extract of the intestine of the edible Atlantic sea cucumber, Cucumaria frondosa, with potent anti-inflammatory effects. In the current study, we investigated Frondanol as a putative anti-inflammatory compound in an experimental model of colonic inflammation. C57BL/6J male black mice (C57BL/6J) were given 3% dextran sodium sulfate (DSS) in drinking water for 7 days to induce colitis. The colitis group received oral Frondanol (100 mg/kg body weight/per day by gavage) and were compared with a control group and the DSS group. Disease activity index (DAI) and colon histology were scored for macroscopic and microscopic changes. Colonic tissue length, myeloperoxidase (MPO) concentration, neutrophil and macrophage marker mRNA, pro-inflammatory cytokine proteins, and their respective mRNAs were measured using ELISA and real-time RT-PCR. The tissue content of leukotriene B4 (LTB4) was also measured using ELISA. Frondanol significantly decreased the DAI and reduced the inflammation-associated changes in colon length as well as macroscopic and microscopic architecture of the colon. Changes in tissue MPO concentrations, neutrophil and macrophage mRNA expression (F4/80 and MIP-2), and pro-inflammatory cytokine content (IL-1β, IL-6 and TNF-α) both at the protein and mRNA level were significantly reduced by Frondanol. The increase in content of the pro-inflammatory mediator leukotriene B4 (LTB4) induced by DSS was also significantly inhibited by Frondanol. It was thus found that Frondanol supplementation attenuates colon inflammation through its potent anti-inflammatory activity.